Pengaruh Pola Asuh Orang Tua Terhadap Kepercayaan Diri Peserta Didik XI MIPA Di SMA Negeri 2 Salatiga - Wiguna, Ramadhan Adi (Universitas Muhammadiyah Metro, 2023)
Self-confidence cannot be separated from the influence of the role of parents in raising their children. Parents are parties who have an essential role in organizing, managing, and educating the process of child growth and development. In the reasoning, there is a significant influence between parenting and self-confidence. This study aims to determine the significance of parenting patterns' impact on students' self-confidence in class XI MIPA at SMA Negeri 2 Salatiga. The study was conducted on 174 class XI MIPA SMA Negeri 2 Salatiga students. The analysis technique used was simple linear regression, which was processed with the help of SPPS version 26.0 for Windows. The results showed that the effective contribution of parenting patterns to self-confidence was 11.2%, and the remaining 88.8% came from other variables that had not been studied. The results of the ANOVA test obtained the value of count = = 4.658 and table = 1.97369 with a significance level of 0.00 <0.05. So from the results, it can be concluded that the hypothesis,